Rice bran: from waste to nutritious food ingredients - Tan, Bee Ling; Norhaizan, Mohd Esa; Chan, Lee Chin (Multidisciplinary Digital Publishing Institute, 2023)
Rice (Oryza sativa L.) is a principal food for more than half of the world’s people. Rice is predominantly consumed as white rice, a refined grain that is produced during the rice milling process which removes the bran and germ and leaves the starchy endosperm. Rice bran is a byproduct produced from the rice milling process, which contains many bioactive compounds, for instance, phenolic compounds, tocotrienols, tocopherols, and γ-oryzanol. These bioactive compounds are thought to protect against cancer, vascular disease, and type 2 diabetes. Extraction of rice bran oil also generates various by-products including rice bran wax, defatted rice bran, filtered cake, and rice acid oil, and some of them exert bioactive substances that could be utilized as functional food ingredients. However, rice bran is often utilized as animal feed or discarded as waste. Therefore, this review aimed to discuss the role of rice bran in metabolic ailments. The bioactive constituents and food product application of rice bran were also highlighted in this study. Collectively, a better understanding of the underlying molecular mechanism and the role of these bioactive compounds exerted in the rice bran would provide a useful approach for the food industry and prevent metabolic ailments.